Bridging the Gap: Why Digital Business Degrees Are the New Premium Ticket to the Modern Job Market - Riris Ananda; Faikul Farul (Program Studi Bisnis Digital Fakultas EKonomi dan Bisnis Universitas PGRI Jombang, 2026)
The rapid acceleration of the global digital economy has fundamentally shifted the corporate landscape, creating a critical demand for professionals who possess a blend of technological proficiency and strategic business acumen. Traditional business curricula often fail to address these cross-disciplinary requirements, leaving a notable skills gap in the modern workforce. This article examines the emergence of dedicated Digital Business degrees as a pivotal solution to this challenge. By analyzing current job market trends, curriculum structures, and employer expectations, this paper highlights how specialized education in digital business equips graduates with high-demand competencies such as data analytics, digital marketing strategy, and e-commerce management. Ultimately, the study positions the Digital Business degree not merely as an educational trend, but as a premium credential that significantly enhances graduate employability and future-proofs careers in an increasingly automated world.